Ryzyko macierzyństwa a problematyka zwrotu świadczeń nienależnych na gruncie prawa ubezpieczeń społecznych - Napiórkowska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2024)
The subject of the study is the issue relating to the recovery of undue benefits under social insurance law in relation to the risk of maternity. However, the study also concerns benefits related to temporary incapacity for work. Most often, the use of maternity benefit is preceded by the use of sickness benefit. The article draws attention to the relationship between Article 66 (2) of the Act on cash benefits under social insurance in the case of sickness and maternity and Article 84 of the Act on the social insurance system. A large part of the study deals with the issue of contesting the title of social insurance or the inflated contribution calculation basis in the context of attempts made by some people to “create” a specific title of social insurance and pretend its existence, or, to declare a high contribution calculation basis in order to receive disproportionately high benefits, often against the rules of rationality, from the beginning of the activity, without income to cover high contributions. In Poland, according to the Polish Social Insurance Institution, the most common reason for concluding that a maternity benefit is an undue benefit is that the recipient was not subject to social insurance scheme. In this context, the premise of deliberate misrepresentation of the benefit recipient to the pension authority has become the subject of consideration. The existence of circumstances fulfilling this premise is related to the obligation to return the undue benefit.
Keywords: maternity; undue benefit; recovery of undue benefits; social insurance scheme